2016
DOI: 10.1080/19476337.2016.1172261
|View full text |Cite
|
Sign up to set email alerts
|

Thermal gelling properties and mechanism of porcine myofibrillar protein containing flaxseed gum at various pH values

Abstract: Flaxseed gum (FG) was reported to enhance the water holding capacity and thermal stability of myofibrillar protein (MP). However, the role of pH in the interaction of MP and FG is still unclear. The aim of this study was to evaluate gelling properties and physicochemical properties of MP-FG gel at various pH values, to explore the mechanism. The results reveal that higher pH value could increase the water holding capacity of MP-FG gels and the highest gel strength is achieved at pH 6.5. Raman spectroscopic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Flaxseed gum (FG), extracted from flaxseed, has enjoyed a significant interest from food and pharmaceutical industry. Nowadays, FG draws more and more attention not only because of its excellent water‐holding capacity but also its unique gel properties (Pan et al ., ). It is reported that the concentration of FG was in positive correlation with the apparent viscosities of the starch gels; thus, it is always added into starch gels to increase the apparent viscosity (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Flaxseed gum (FG), extracted from flaxseed, has enjoyed a significant interest from food and pharmaceutical industry. Nowadays, FG draws more and more attention not only because of its excellent water‐holding capacity but also its unique gel properties (Pan et al ., ). It is reported that the concentration of FG was in positive correlation with the apparent viscosities of the starch gels; thus, it is always added into starch gels to increase the apparent viscosity (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Non‐meat ingredients, especially legume proteins, are regarded as potential substitutes to improve the quality and nutritional value of meat products. This has attracted the attention of increasing numbers of scientists 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Fractionating flax seed to kernel and hull—representing 63% and 37% of the total seed weight [ 15 ], respectively—is of great importance, as it allows an oil-rich fraction (kernel) and a gum-rich fraction (hull) to be obtained, thus reducing the downstream processing cost and increasing the profitability. Numerous studies have shown interest in valorizing flaxseed hulls by extracting the residual oil [ 16 ], proteins and polyphenols [ 17 , 18 ], as well as SFG, with some potential applications [ 19 , 20 , 21 , 22 , 23 , 24 ]. Investigating other health-related benefits of SFG—such as its antioxidant potential, which has not been described before—is interesting, as it may lead to the replacement of some synthetic antioxidants, which are more and more restricted by legislation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%